Is a full component revision necessary for isolated tibial loosening?. (June 2020) - Martin, J. Ryan; Geary, Michael B.; Ransone, Michael; Macknet, David; Fehring, Keith; Fehring, Thomas
Abstract : Aims: Aseptic loosening of the tibial component is a frequent cause of failure in primary total knee arthroplasty (TKA). Management options include an isolated tibial revision or full component revision. A full component revision is frequently selected by surgeons unfamiliar with the existing implant or who simply wish to "start again". This option adds morbidity compared with an isolated tibial revision. While isolated tibial revision has a lower morbidity, it is technically more challenging due to difficulties with exposure and maintaining prosthetic stability. This study was designed to compare these two reconstructive options. Methods: Patients undergoing revision TKA for isolated aseptic tibial loosening between 2012 and 2017 were identified. Those with revision implants or revised for infection, instability, osteolysis, or femoral component loosening were excluded. A total of 164 patients were included; 88 had an isolated tibial revision and 76 had revision of both components despite only having a loose tibial component. The demographics and clinical and radiological outcomes were recorded. Results: The patient demographics were statistically similar in the two cohorts. The median follow-up was 3.5 years (interquartile range (IQR) 1 to 12.5). Supplementary femoral metaphyseal fixation was required in five patients in the full revision cohort. There was a higher incidence of radiological tibial loosening in the full component revision cohort at the final follow-up (8 (10.5%) vs 5 (5.7%); p = 0.269). Three patients in the full component revision cohort developed instability while only one in the isolated tibial cohort did. Three patients in the full revision cohort developed a flexion contracture greater than 5° while none in the isolated tibial cohort did. Conclusion: Isolated tibial revision for aseptic tibial loosening has statistically similar clinical and radiological outcomes at a median follow-up of 3.5 years, when compared with full component revision. Substantial bone loss can occur when removing a well-fixed femoral component necessitating a cone or sleeve. Femoral component revision for isolated tibial loosening can frequently be avoided provided adequate ligamentous stability can be obtained. Cite this article: Bone Joint J 2020;102-B(6 Supple A):123–128.